Uranium removal from tin smelter slag by bisulfate fusion and acidic leaching - Erik Prasetyo Prasetyo; Sonia Saraswati Meiliastri; Kurnia Trinopiawan; Yayat Iman Supriyatna; Fathan Bahfie; Giyatmi Giyatmi (National Research and Innovation Agency (BRIN), 2020)
Slag as secondary product (waste) of tin smelter still contains not only valuable elements e.g. Ti, Nb, Ta, Zr, Hf and rare earth elements, but also radioactives such as Th and U, wich are accumulated in the slag phase during the smelting. Due to valuable element content, the slag becomes major of interest in mineral processing industries, hence the slag needs to be decontaminated before it could be processed further.Common approach to reduce U content from the slag using leaching process is considered ineffective due to association of U with refractory elements e.g. Si and Ti in the slag. To break down the refractory phases, the fusion approach by using fusing agent is required in order to release U so that they could be leached out using mild lixiviant.In this research, potassium hydrogen sulfate (KHSO4) and sulfuric acid was used as fusing agent and lixiviant, respectively. The parameters studied includes molar ratio between fusing agent and refractory elements in slag, fusion temperature, fusion time, sulfuric acid concentration in lixiviant and pulp density during leaching stage. The studies so far demonstrated that optimum condition in U removal occurred at fusion temperature 400 °C, fusion time 2 hours, molar ratio of potassium hydrogen sulfate to tin slag 5, sulfuric acid concentration 2 M and pulp density 15 ml/gr. The maximum recovery of U was 85.6%, which was significant compared to the results using direct leaching without fusion (0.1%).